Non-Governmental Organizations - Factors for Local Development - Marton BALOGH (Transylvanian Review of Administrative Sciences, 2012)
This article aims at creating a correlation between the non-governmental (non-profit sector) and local development in order to highlight the role that these entities play in this process. The article will particularly emphasize the impact of these actors on the local development of Cluj- Napoca and argues in favor of a paradigm shift concerning how local development policies are currently implemented. Through this approach we want to propose a paradigm shift with respect to the development policies implemented in local communities for the purposes of capitalizing aspects of quality of life and diversity of services addressed to the population to the detriment of classic indicators of development: paved streets, foreign investment etc.